Detection of Oil in Water Using Photodiode and Internet of Things - Nur Nazifa Che Samsuria; Wan Zakiah Wan Ismail; Mior Fakhrul Hazim Mior Abdul Halil; Ab Aziz, Nor Azlina; Anith Khairunnisa Ghazali; Wan Maryam Wan Ahmad Kamil (International Journal of Integrated Engineering, 2025)
Oil spills in irrigation ditches can have severe environmental and agricultural consequences. We proposes a system that can detect oil spill using a photodiode and an Internet of Things (IoT) platform to enable real-time monitoring. The system integrates a blue light-emitting diode (LED), a photodiode, and an ESP32 microcontroller, which measures resistance changes as an indicator of oil presence in water. Experimental evaluations were conducted by varying the distance between the light source and sensor (6 cm to 9 cm), oil volume (50 mL to 200 mL), and exposure time (1-6 hours). Results indicate that resistance values for oil-free water range from 300 kΩ to 500 kΩ, while oil-contaminated water consistently exhibits resistance below 18 kΩ. The optimal distance for accurate oil detection was determined to be 8 cm, maintaining stable resistance values. Increasing oil volume and prolonged exposure time reduced light penetration, causing a decrease in resistance. Real-time monitoring via the Blynk application provides immediate alerts when oil is detected. The proposed system offers a low-cost, efficient, and scalable solution for early oil spill detection in agricultural irrigation systems, minimizing environmental damage and improving water quality management.